Postoperative Delirium, Learning, and Anesthetic Neurotoxicity: Some Perspectives and Directions - Mutch, W. Alan C.; El-Gabalawy, Renée M.; Graham, M. Ruth (Frontiers in Neurology, 2018)
Evidence of anesthetic neurotoxicity is unequivocal when studied in animal models. These findings have translated poorly to the clinical domain when equated to post-operative delirium (POD) in adults, and cognitive dysfunction (POCD) in either children or the elderly. In this perspective we examine various reasons for the differences between animal modeling of neurotoxicity and the clinical situation of POD and POCD and make suggestions as to potential directions for ongoing research. We hypothesize that the animal anesthetic neurotoxicity models are limited, in part, due to failed scaling correction of physiological time. We posit that important insights into POCD in children and adults may be gleaned from studies in adults examining alterations in perioperative management designed to limit POD. In this way POD is used as the proxy for POCD rather than neuronal dropout or behavioural abnormalities in animal models that may or may not be proxies for the human condition. We argue that it is time to move beyond animal models of neurotoxicity to directly examine these problems in well conducted clinical trials with comprehensive pre-operative neuropsychometric and psychiatric testing, high fidelity intra-operative monitoring of physiological parameters during the anesthetic course and post-operative assessment of subthreshold and full classification of POD. In this manner we can ‘model ourselves’ to better understand these important and poorly understood conditions.